Some aspects of change in agrarian structure - "Mishra , G . P" (New Delhi, 1977)
This book covers the following topics Agrarian structure and weaker sections; Process of Income Distribution in Agriculture; A note on Capitalist Farming; Planning in Land reforms etc.
Keywords: Agrarian structure